2010
DOI: 10.1039/c000813c
|View full text |Cite
|
Sign up to set email alerts
|

Peptide conjugate hydrogelators

Abstract: 5Molecular gelators are currently receiving a great deal of attention. These are small molecules which, under the appropriate conditions, assemble in solution to, in the majority of cases, give long fibrillar structures which entangle to form a three-dimensional network. This immobilises the solvent, resulting in a gel. Such gelators have potential application in a number of important areas from drug delivery to tissue engineering. Recently, the use of peptide-conjugates has become 10 prevalent with oligopepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
102
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(102 citation statements)
references
References 201 publications
(455 reference statements)
0
102
0
Order By: Relevance
“…By far the most studied group of aromatic peptide conjugates are peptides capped with the fluorenylmethyloxycarbonyl moiety a Present address: School of Physics and Astronomy, E. C. Stoner building, University of Leeds, Woodhouse Lane, Leeds, LS2 9JT, UK. e-mail: A.Aufderhorst-Roberts@leeds.ac.uk (Fmoc) [12]. Hydrogels can also be formed from Fmocamino acids, with Fmoc-Tyrosine being the most commonly studied [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…By far the most studied group of aromatic peptide conjugates are peptides capped with the fluorenylmethyloxycarbonyl moiety a Present address: School of Physics and Astronomy, E. C. Stoner building, University of Leeds, Woodhouse Lane, Leeds, LS2 9JT, UK. e-mail: A.Aufderhorst-Roberts@leeds.ac.uk (Fmoc) [12]. Hydrogels can also be formed from Fmocamino acids, with Fmoc-Tyrosine being the most commonly studied [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to control the size and shape of nano-and micrometer size objects that rely on selective solvent techniques in the self-assembly of block copolymers will not be discussed here. [60][61][62][63][64][65][66][67][68][69][70][71][72][73] Supramolecular multicomponent gels, [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] or orthogonal self-assembly, [90][91][92][93][94][95][96][97] self-sorting [98][99][100][101][102][103][104] and chiral amplification strategies 105 in multicomponent supramolecular polymers will not be covered in detail, and the interested reader is referred to the recent literature and review articles.…”
mentioning
confidence: 99%
“…The importance of aromatic stacking interactions has been thoroughly studied, and an N-terminal Fmoc group is more than a simple hydrophobic group. It facilitates self-assembly and gelation through π-π stacking for a wide variety of aromatic peptide amphiphiles [165,166]. A recent study comparing two aromatic peptide amphiphiles with identical peptide sequences but varied aromatic groups (Fmoc and naphthyl) found that the Fmoc peptide gels at above 0.1% while the naphthyl peptide gels at concentrations as low as 0.01% [167].…”
Section: Aromatic Peptide Amphiphilesmentioning
confidence: 98%